1973
DOI: 10.1136/bjo.57.8.584
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented paravenous retino-choroidal atrophy. Helicoid retino-choriodal atrophy.

Abstract: The occurrence of bilateral patchy retino-choroidal atrophy in relation to the retinal venous system has been described as "retino-choroiditis radiata" (Brown, I937; HsinHsiang, I948), "chorio-retinitis striata" (Kraffel, I955), and "pigmented paravenous choroidal atrophy" (Weve, I957). The reported examples of this curious affection of the fundus all came to light as incidental findings on routine ophthalmoscopy. We wish to record a further example of this condition which was uncovered in the same way.Case re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…Fluorescein studies in young patients with this entity revealed RPE atrophy with preservation of the choroidal vasculature underlying the atrophic RPE (10). In patients with a more advanced stage of the disease, choroidal atrophy has been observed in the involved areas (15).…”
Section: Histopathology and Attributesmentioning
confidence: 99%
“…Fluorescein studies in young patients with this entity revealed RPE atrophy with preservation of the choroidal vasculature underlying the atrophic RPE (10). In patients with a more advanced stage of the disease, choroidal atrophy has been observed in the involved areas (15).…”
Section: Histopathology and Attributesmentioning
confidence: 99%
“…Patients with analogous fundus changes were described by several other authors (HsinHsiang, 1948;Archer, Krill and Ernest, 1972;Chisholm and Dudgeon, 1973;Francois and De Roucke, 1974;Pearlman et al, 1975Pearlman et al, , 1978and Skalka 1979). Noble and Carr (1983) reported the longest follow-up study of 21 years.…”
Section: Introductionmentioning
confidence: 95%
“…[12][13][14][15] Though some parts of the retina in this patient showed chorioretinal atrophy the marked perivascular pigment aggregations and chorioretinal atrophy were similar to that of the disease.…”
Section: Discussionmentioning
confidence: 97%